HYBRID DESIGN PATCH ANTENNA FOR X-BAND SATELLITE COMMUNICATION (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This study presents a novel approach to the development and application of a rectangular patch antenna optimized for X-band satellite communication operations. The antenna’s performance is enhanced through geometry refinement and the strategic introduction of slots. A novel hybrid design is proposed, combining series and parallel patch antenna arrays in a four-element structure to improve gain, impedance matching, and directivity. These findings offer practical implications for satellite applications, spanning areas such as radar systems, telecommunications, and diverse radio wave applications, including cognitive radio. The simulation and measurement results show a close resemblance for both resonance frequencies at 9.5 GHz, indicating acceptable matching. In terms of the measured S11, two resonance frequencies with excellent matching at 9.018 GHz (S11 = -34.45 dB) and 10.31 GHz (S11 = -21.2 dB). On the other hand, for the simulated S11, there is a resonance frequency at 9.5 GHz with good matching and an S11 value of -35.8 dB. These results indicate that our implemented antenna network is multi-resonant, demonstrating satisfactory matching for multiple frequencies within the X-band with only one antenna array.
Keywords: Antenna arrays; Design optimization; Patch antennas; X-band frequencies; Satellite communication